Spoken language modeling with discrete units - Visser, Nicolaas Floris (Stellenbosch : Stellenbosch University, 2025)
Visser, N. F. 2025. Spoken language modeling with discrete units. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/2d364ad0-2a7b-4a35-b6c6-bc0db74702ed